1995
DOI: 10.1016/s0006-3495(95)80346-2
|View full text |Cite
|
Sign up to set email alerts
|

A look at membrane patches with a scanning force microscope

Abstract: We combined scanning force microscopy with patch-clamp techniques in the same experimental setup and obtained images of excised membrane patches spanning the tip of a glass pipette. These images indicate that cytoskeleton structures are still present in such membrane patches and form a strong connection between the membrane and the glass wall. This gives the membrane patch the appearance of a tent, stabilized by a scaffold of ropes. The lateral resolution of the images depends strongly on the observed structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 18 publications
1
32
1
Order By: Relevance
“…High-resolution images of membranes in patch pipettes have been presented previously (22,23,25,26), and it has been shown that rapid changes in voltage can cause rapid submicrometer movements of the suspended part of the membrane patch (27)(28)(29)(30). Our study shows that prolonged depolarization of a membrane patch in a borosilicate pipette can lead to substantial displacement of the membrane patch into the pipette and that this displacement correlates in time with the activation of MS channels in the same patch.…”
Section: Discussionmentioning
confidence: 53%
“…High-resolution images of membranes in patch pipettes have been presented previously (22,23,25,26), and it has been shown that rapid changes in voltage can cause rapid submicrometer movements of the suspended part of the membrane patch (27)(28)(29)(30). Our study shows that prolonged depolarization of a membrane patch in a borosilicate pipette can lead to substantial displacement of the membrane patch into the pipette and that this displacement correlates in time with the activation of MS channels in the same patch.…”
Section: Discussionmentioning
confidence: 53%
“…It may involve degradation of cytoskeleton elements 17 that are known to be included in the inside-out patch. 18 Although both oleoyl-CoA and PIP 2 rapidly activated K ATP channels after partial rundown, their rate of washout was very slow. After a 15-minute period of exposure to either of these molecules, almost no rundown of K ATP channels was observed during 30 minutes of washout with divalent-free solution ( Figure 1B, arrow).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the regulation of myocardial KATP channels resembles the modulation of Nae and Cl-channels by actin filament disrupters, which can also proceed in excised membrane patches (Cantiello et al 1991;Prat et al 1995;Udrovinas, Shander & Makielski, 1995). This, however, does not necessarily mean that the action of actin filament disrupters could occur in a 'cytosol-free' environment since membrane patches do not consist of just the plasmalemma, but are composed of membrane-covered cytoplasm with cytoskeletal structures (Ruknudin et al 1991;Horber et al 1995). It has been proposed previously that actin, and actin A a ATP (200 1sM) binding proteins, are linked to various transport proteins including the ac-subunit of the Na+,K+-ATPase (Nelson & Veshmock, 1987), Na+ and Ca2+ channels in the brain (Srimivasan, Elmer, Davis, Bennett & Angelides, 1988;Johnson & Byerly, 1993), NMDA channels in the hippocampal neurons (Rosenmund & Westbrook, 1993), Nae and Cl channels in kidney (Cantiello et al 1991;Suzuki et al 1993) and the cystic fibrosis transmembrane conductance regulator (Prat et al 1995).…”
Section: Resultsmentioning
confidence: 99%